Kepastian Hukum Terhadap Kendaraan Yang Didaftarkan Atas Nama Persekutuan Komanditer - Sihite, Sri Rumada (KANJOLI Business Law Review, 2023)
Lawful and reasonable agreement. However, registering the motorized vehicle has a legal consequence that the second party enters their capital in the form of goods, in this case the truck fleet, another problem that arises from the agreement is the consequences in the event of a loss to the company. More specifically regarding the responsibility of the Limited Partnership for motorized vehicles on behalf of the Limited Partnership where in essence the vehicle is owned by an individual. The ambiguity that arises is as if the motorized vehicle can be categorized as assets owned by the Limited Partnership so that the curator can carry out an inventory of the assets of the Limited Partnership. The research method used in this paper is normative legal research. This research is directed to be able to provide a description of the implications of legal certainty for vehicles registered on behalf of limited partnerships. Based on this description, the legal gaps in this study are: legal certainty for registered vehicles, the validity of agreements made by limited partnerships with new members, and legal consequences in the event of bankruptcy in limited partnerships for members. Legal certainty for vehicles registered on behalf of the vehicle on behalf of the Limited Partnership. Success Kencana Express and the letters used legally. The validity of the truck fleet ownership membership agreement with CV. Success Kencana Eexpress. Where the agreement is done under the hand. Article 1338 of the Civil Code states that the agreement remains in effect as the law that made it because the legal conditions for the agreement have been met. Legal consequences if there is a loss to CV. Success Kencana Eexpress is mentioned in Article 8 in the membership agreement letter for ownership of the truck fleet with CV. Kencana Abadi's Success are matters that have not been sufficiently regulated/irregular in a statement letter and membership agreement will be arranged by deliberation and consensus. In this provision it is stated that if there is something that is not explained, including parties who feel disadvantaged.